Pengaruh Riba dan Bunga terhadap Alokasi Sumber Daya dalam Ekonomi Makro Islam - M. Nurul Furqon (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to analyze the influence of usury and interest on resource allocation in the perspective of Islamic macroeconomics. In the conventional economic system, interest serves as the main instrument in the financial mechanism, but this practice is considered to cause distortion because more capital flows to the speculative financial sector than to the productive real sector. In Islamic view, usury is prohibited because it creates social injustice and economic imbalance. Islamic economics offers an alternative paradigm through a system without usury based on justice ('adl), balance (mizan), and productivity (ihsan). This research uses a descriptive qualitative approach with a literature study method, which is sourced from primary literature such as the Qur'an, Hadith, as well as the works of Islamic economic thinkers (Chapra, Siddiqi, Kahf), and secondary literature such as scientific journals, books, and reports of Islamic financial institutions. Data analysis was carried out using content analysis and thematic approaches, following the model of Miles & Huberman (1994) through the stages of reduction, presentation, and drawing conclusions. The results show that the interest-based system causes distribution inequality, inefficient capital allocation, and monetary instability, while the Islamic economic system with the principle of profit and loss sharing creates an optimal, fair, and aligned resource allocation with Islamic macroeconomic objectives. Thus, the system without usury has proven to be more able to maintain a balance between the real and monetary sectors and support sustainable economic development based on justice.